2021
DOI: 10.3390/microorganisms9020319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil and Water Conservation Measures on Soil Microbial Communities in a Citrus Orchard of Southeast China

Abstract: Soil microbes play a crucial role in ecosystem function. Here, the effects of soil and water conservation measures on soil microbial community structures, biodiversity, and co-occurrence networks are investigated and compared. We sampled soils at three different depths (0–10 cm, 10–20 cm and 20–40 cm) in a citrus orchard that uses long-term soil and water conservation measures, which includes Bermuda grass strip intercropping (BS), Bermuda grass full coverage (BF), Radish–soybean crop rotation strip intercropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Soil microbial community in citrus orchards play an important role in releasing soil nutrients and preventing plant diseases [3] and play an important role in promoting citrus growth and health [12]. In recent years, there have been many studies about the effects of irrigation regime, tillage method, citrus tree tissues, and citrus disease on microbial community [13][14][15]. Nevertheless, the relationship between nitrogen application rate, citrus yield, and microbial community should also be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbial community in citrus orchards play an important role in releasing soil nutrients and preventing plant diseases [3] and play an important role in promoting citrus growth and health [12]. In recent years, there have been many studies about the effects of irrigation regime, tillage method, citrus tree tissues, and citrus disease on microbial community [13][14][15]. Nevertheless, the relationship between nitrogen application rate, citrus yield, and microbial community should also be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The red soil hilly region in southern China is enriched in rainfall and heat resources and possesses tremendous potential ecosystem productivity (Wu et al., 2021). The hilly area of the region accounts for about 60.6% of the land area in southern China and has been facing severe soil and water loss owing to the strong rainfall erosivity, high soil erodibility, and inadequate land management for a long period (Tu, Xie, Zheng, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the bacterioplankton community can also reflect the ecological environment of the river to a certain extent and is an ideal indicator that can be used to monitor the ecological impacts of human activities on the functional characteristics of the river water environment [3]. Previous work has shown that human influences affect microbiome composition [4][5][6], microbe-microbe interactions [7,8] and microbe-host interactions [3,9,10]. Although it is well documented that such changes in network structure affect ecosystem functioning and stability, little is known about the link between human activity intensity and the stability of these microbial systems and whether and how the ecological networks, particularly bacterioplankton molecular ecological networks, will change under human activity intensity change scenarios.…”
Section: Introductionmentioning
confidence: 99%